2005
DOI: 10.1007/s00018-004-4423-2
|View full text |Cite
|
Sign up to set email alerts
|

Association, mutual stabilization, and transcriptional activity of the STRA13 and MSP58 proteins

Abstract: STRA13 is a hypoxia-inducible bHLH transcription factor implicated in the pVHL/HIF, TGF-beta, and Jak/STAT pathways. To further characterize the STRA13 protein-interacting network and mechanisms of STRA13-dependent transcription, we utilized yeast two-hybrid screening. Here we report on STRA13 interaction with the cell cycle-associated transcription factor MSP58. We demonstrated that the basic domain of STRA13 and the FHA domain of MSP58 are essential for this association. We performed phospho-peptide mapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 63 publications
1
24
0
1
Order By: Relevance
“…These results highlight the critical importance of the STRA13 C-terminus for the transcriptional repression. As the STRA13 C-terminal region was previously associated with protein-protein interaction (Sun and Taneja, 2000;Ivanova et al, 2004Ivanova et al, , 2005, the obtained data suggested a cooperation between STRA13 and other transcriptional regulator(s) on the STAT1 promoter.…”
Section: Stra13 Represses the Stat1 Promoter Independently Of E-boxesmentioning
confidence: 52%
See 2 more Smart Citations
“…These results highlight the critical importance of the STRA13 C-terminus for the transcriptional repression. As the STRA13 C-terminal region was previously associated with protein-protein interaction (Sun and Taneja, 2000;Ivanova et al, 2004Ivanova et al, , 2005, the obtained data suggested a cooperation between STRA13 and other transcriptional regulator(s) on the STAT1 promoter.…”
Section: Stra13 Represses the Stat1 Promoter Independently Of E-boxesmentioning
confidence: 52%
“…For Western blot, cells were lysed in RIPA buffer and proteins fractionated as described earlier (Ivanova et al, 2004). STRA13 antibodies against the endogenous protein were ordered from Washington Biotechnology (Washington, DC) and validated in our previous study (Ivanova et al, 2005). STAT1 and STAT3 antibodies were purchased from Santa Cruz Biotechnology (Santa Cruz, CA, USA).…”
Section: Northern and Western Blot Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the C terminus of PTEN has been shown to bind to the nucleolar 58-kDa microspherule protein (MSP58), which forms a complex with the hypoxia-inducible transcription factor DEC1 (differentiated embryo-chondrocyte expressed gene 1) implicated in the pVHL-HIF pathway under chronic hypoxia. [36][37][38] It is worth investigating whether these potential binding partners interact with PTEN in EBs and whether they are involved in PHD2 and HIF-2Ī± regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies showed that, in the nucleus, MSP58 could function to regulate transcription through its interactions with the transcription factors Daxx, STRA13, and the RNA-binding protein FMR (Lin et al, 2002;Ivanova et al, 2005;Davidovic et al, 2006). A study showed that TOJ3, the quail homologue of MSP58, displayed transformation activity in juntransformed fibroblasts (Bader et al, 2001), whereas the tumor suppressor gene PTEN could suppress its transforming activity (Okumura et al, 2005).…”
mentioning
confidence: 99%